Full solar spectrum available hierarchical porous ZIF/Fe-DCA (70) co-assisted by isolated Fe and rich defects for boosted environmental remediation efficiency - Lan, Yufan; Luo, Xiao; Liang, Jing; Wang, Song; Han, Wuli; Li, Qiang; Cai, Jingpeng (Journal of catalysis, 2024)
[Display omitted] •The ingenious cationic defects engineering and molecular-scale cages effect are working together to harvest rich defects and high-density isolated Fe on the MOF skeleton, rearranging/optimizing the electronic structure of the catalyst and further providing huge benefits to the photocatalytic activity.•The obtained ZIF/Fe-DCA(70) has broaden the light absorption ability to NIR range (≧780 nm) with tremendous potential for utilization of full solar spectrum, and excellent photodegradation efficiency is observed both in VIS and NIR light.•This manuscript investigates the mechanism and probable causes of localized surface plasmon resonance (LSPR) on catalyst surface.•The photothermal effect provides assistance on the photocatalysis process to achieve a more efficient solar light utilization, and the photo-thermal energy conversion was recorded by infrared thermography visually.•A satisfactory purifying efficiency was detected on the mixed antibiotic and dyes solutions under real sunlight irradiation, revealing the practicality and broad-spectrum property of catalyst. The cationic defects engineering and molecular-scale cages effect work together to harvest rich defects and high-density isolated Fe on ZIF, endowing ZIF/Fe-DCA (70) with exposed active sites, facilitating photogenerated carrier separation and optimizing electronic structure. The LSPR effect, intermediated energy band and photothermal transition broaden the light absorption to NIR range with Eg = 2.15 eV. Removal rates for TC (60 mg/L), MB (10 mg/L), MO (10 mg/L) and GV (10 mg/L) are 93 %/86.3 %, 98.2 %/85.1 %, 83.7 %/70.2 % and 82 %/68 % after Vis/NIR irradiation, respectively. A satisfactory purifying efficiency was also detected on the mixed pollutants solution under real sunlight. Besides, the infrared thermography was employed to verify the photothermal conversion visually. The ‧O2−, 1O2, and triplet state are the most effective active species, and the ‧OH and h+ both apparently participate in the photodegradation. This study provides effective design ideas involving single atomic co-catalyst and defects into MOFs as full-spectrum photocatalysts to repair environment.